Legal Protection for Medical Recorders and Health Information Personnel in the Management of Electronic Medical Records: Perlindungan Hukum Bagi Tenaga Perekam Medis dan Informasi Kesehatan dalam Pengelolaan Rekam Medis Elektronik - Wardana, I Wayan Dody Putra; Sudarsana, I Gede Diki; Murcittowati, Putu Ayu Sri; Wirajaya, Made Karma Maha (Procedia of Engineering and Life Science, 2025)
Medical recorders and health information workers are one type of health workers who have the authority to manage electronic medical record services in health service facilities in accordance with Minister of Health Regulation Number 24 of 2022 concerning medical records. Electronic medical records in their application pose risks in terms of privacy and confidentiality considering that they are vulnerable to changes in data, duplication of data, transfer and buying and selling by irresponsible people. In addition, intentional or unintentional negligence in managing medical record documents makes this profession very vulnerable to lawsuits and legal sanctions in carrying out its authority. Seeing these problems, legal certainty and protection is needed for medical record and health information workers in carrying out their professional principles in managing electronic medical record services. This research was carried out to find out how legal protection is for medical recording and health information workers in managing electronic medical record services. The method in this research is a normative legal method with a statutory approach and a conceptual approach. Based on the results of this research, it is known that medical recording and health information workers have legal certainty and protection, both preventive and repressive, in accordance with the mandate of the state constitution in the 1945 Constitution and confirmed in Law Number 17 of 2023 concerning Health and Minister of Health Regulation Number 55 of 2013 concerning the Implementation of Work Medical. As a profession that exercises its authority, medical recorders and health information have legal implications if they commit a violation. In this way, medical recorders and health information workers have received legal protection and legal implications in maintaining electronic medical records as long as they meet professional standards and health service standards.